A nested square-shape dielectric resonator for microwave band antenna applications - Ullah, Ubaid; Mabrouk, Ismail Ben; Al-Hasan, Muath; Nedil, Mourad; Ain, Mohd Fadzil (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper, a nested square-shape dielectric resonator (NSDR) has been designed and investigated for antenna applications in the microwave band. A solid square dielectric resonator (SSDR) was modified systematically by introducing air-gap in the azimuth (ϕ-direction). By retaining the square shape of the dielectric resonator (DR), the well-known analysis tools can be applied to evaluate the performance of the NSDR. To validate the performance of the proposed NSDR in antenna applications, theoretical, simulation, and experimental analysis of the subject has been performed. A simple microstrip-line feeding source printed on the top of Rogers RO4003 grounded substrate was utilized without any external matching network. Unlike solid square DR, the proposed NSDR considerably improves the impedance bandwidth. The proposed antenna has been prototyped and experimentally validated. The antenna operates in the range of 12.34GHz to 21.7GHz which corresponds to 56% percentage bandwidth with peak realized gain 6.5dB. The antenna has stable radiation characteristics in the broadside direction. A close agreement between simulation and experimental results confirms the improved performance of NSDR in antenna applications.